2019
DOI: 10.1128/mbio.01533-19
|View full text |Cite
|
Sign up to set email alerts
|

Massive Gene Flux Drives Genome Diversity between Sympatric Streptomyces Conspecifics

Abstract: In this work, by comparing genomes of closely related individuals of Streptomyces isolated at a spatial microscale (millimeters or centimeters), we investigated the extent and impact of horizontal gene transfer in the diversification of a natural Streptomyces population. We show that despite these conspecific strains sharing a recent common ancestor, all harbored significantly different gene contents, implying massive and rapid gene flux. The accessory genome of the strains was distributed across insertion/del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 70 publications
2
70
0
Order By: Relevance
“…Previous 16S rRNA-based phylogeny analyses suggested that 18 strains collected during our various campaigns aimed at isolating actinomycetes from karstic environments belong to the species Streptomyces lunaelactis [ 13 , 14 , 15 ]. However, 16S rRNA is a weak marker for species determination in streptomycetes and we therefore performed MLSA using concatenated full-length sequences of housekeeping genes atpD , gyrB , recA , rpoB , and trpB .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous 16S rRNA-based phylogeny analyses suggested that 18 strains collected during our various campaigns aimed at isolating actinomycetes from karstic environments belong to the species Streptomyces lunaelactis [ 13 , 14 , 15 ]. However, 16S rRNA is a weak marker for species determination in streptomycetes and we therefore performed MLSA using concatenated full-length sequences of housekeeping genes atpD , gyrB , recA , rpoB , and trpB .…”
Section: Resultsmentioning
confidence: 99%
“…However, genome assemblies of some S. albus strains contain many contigs on which some biosynthetic gene clusters (BGCs) might be scattered, thereby resulting in an overestimation of the total number of BGCs [ 9 ]. In a more recent study, Tidjani AR and colleagues showed, by comparative genomics of Streptomyces strains belonging to the same species and isolated at the microscale, that almost-clonal strains can present important genetic content diversity providing them with unique metabolite production capabilities [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…to a previously isolated cluster of strains (identical 16S rRNA gene sequences) (8,14) that was closely related to Streptomyces olivochromogenes DSM 40451 (99.9% identity in 16S rRNA gene sequences) (15). The strains RLB1-33, RPA4-2, and S1D4-11 and Streptomyces mirabilis CSSP107 exhibited identities of 99.9% to 99.2% in their 16S rRNA genes, indicating that they might belong to the same species or constitute sister species.…”
mentioning
confidence: 81%
“…The 11 strains selected showed identical 16S rRNA gene sequences and minimal MLSA divergence. These strains are related to Streptomyces olivochromogenes (strain DSM40451), with an average identity of 99.93% for the 16S rRNA gene sequences (8). A hybrid assembly using Oxford Nanopore technology for scaffolding and Illumina technology for sequence improvement was performed (Table 1).…”
Section: Announcementmentioning
confidence: 99%